2004
DOI: 10.1183/09031936.04.00069604
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal nicotine exposure increases connective tissue expression in foetal monkey pulmonary vessels

Abstract: Among the many deleterious effects of maternal smoking during pregnancy on foetal development, is a higher incidence of persistent pulmonary hypertension. The recent identification of nicotinic acetylcholine receptors (nAChR) on cells of the pulmonary vessel walls suggests that maternal smoking during pregnancy may produce morphological alterations in foetal pulmonary vasculature.Timed-pregnant rhesus monkeys were treated with nicotine (1 mg?kg -1 ?day -1 ) delivered by subcutaneous osmotic mini-pumps from day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 35 publications
8
45
0
5
Order By: Relevance
“…Treatment of pregnant rhesus monkeys with low levels of nicotine designed to simulate the nicotine exposure of pregnant human smokers caused marked increases of levels of a7 nAChR in airway epithelial cells and fibroblasts in fetal monkey lung ( Figures 1A and 1B). There were also increases in collagen and connective tissue in a similar distribution as the increase in a7 nAChR ( Figures 1C-1F) (56)(57)(58). Similar effects of prenatal nicotine exposure increasing lung collagen were also seen in mice (48).…”
Section: Effects Of Prenatal Nicotine Exposure On Lung Development Ansupporting
confidence: 58%
See 1 more Smart Citation
“…Treatment of pregnant rhesus monkeys with low levels of nicotine designed to simulate the nicotine exposure of pregnant human smokers caused marked increases of levels of a7 nAChR in airway epithelial cells and fibroblasts in fetal monkey lung ( Figures 1A and 1B). There were also increases in collagen and connective tissue in a similar distribution as the increase in a7 nAChR ( Figures 1C-1F) (56)(57)(58). Similar effects of prenatal nicotine exposure increasing lung collagen were also seen in mice (48).…”
Section: Effects Of Prenatal Nicotine Exposure On Lung Development Ansupporting
confidence: 58%
“…The increased collagen and decreased elastin may underlie the decreased respiratory compliance observed in some studies in the offspring of mothers who smoked during pregnancy (37)(38)(39). Prenatal nicotine exposure also leads to thickening of walls surrounding airways and pulmonary vessels in monkeys (58), and this has also been reported in offspring of smokers ( Figure 1G) (59,60). In particular, the patterns of collagen expression observed in airways of offspring of smokers are strikingly similar to those observed in lungs of animals exposed just to nicotine (56)(57)(58) (Figure 1G).…”
Section: Effects Of Prenatal Nicotine Exposure On Lung Development Anmentioning
confidence: 99%
“…Previous studies from our laboratory and other laboratories have shown that acetylcholine and M3 receptors are expressed in a wide variety of normal endothelial and epithelial cell types (5)(6)(7)(8)(9)(10)(11)(12)(13). This suggests that cancers derived from these diverse cell types will similarly coexpress acetylcholine and M3 receptors.…”
Section: Resultsmentioning
confidence: 79%
“…[1][2][3][4] Moreover, it has been shown that cigarette smoking may accelerate the progression of renal, pulmonary, and cardiac fibrosis. [5][6][7] The detrimental effects of smoking have beenextensively investigated by studies of direct administration of nicotine, a major pharmacologically active component of tobacco smoke, 8 in animal and in a variety of cell systems. The predominant effects of nicotine in the whole intact animal or human consist of an increase inheart rate (10 to 20 beats/min),blood pressure (5 to 10 mmHg), release of catecholamines and free fatty acids and mobilization of blood sugar.…”
Section: Introductionmentioning
confidence: 99%